2014
DOI: 10.1177/0194599814557467
|View full text |Cite
|
Sign up to set email alerts
|

Role of Polysomnography in the Development of an Algorithm for Planning Tracheostomy Decannulation

Abstract: Polysomnography may be a useful adjunctive study in the process of determining a patient's readiness for decannulation. Our current algorithm for decannulation includes upper airway endoscopy with identification of levels of obstruction, followed by surgical correction of those obstructions; capped PSG to determine patency of the airway and help assess lung function; and overnight intensive care unit admission for capping trial, with decannulation the following day if well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 10 publications
5
39
0
6
Order By: Relevance
“…Based on our results in combination with literature review, we propose an algorithm for weaning nocturnal HMV and decannulation (Figure ). Our algorithm combines the use of daytime capping, and downsizing the tracheostomy to determine readiness for decannulation followed by an overnight capped PSG as a final confirmation.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Based on our results in combination with literature review, we propose an algorithm for weaning nocturnal HMV and decannulation (Figure ). Our algorithm combines the use of daytime capping, and downsizing the tracheostomy to determine readiness for decannulation followed by an overnight capped PSG as a final confirmation.…”
Section: Discussionmentioning
confidence: 92%
“…A capped PSG can help provide the final confirmation that the child is ready for decannulation and is frequently performed prior to decannulation . However, there are no well‐established PSG parameters that correlate with a successful outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although various protocols have been reported, there is no standardized approach to weaning chronic mechanical ventilation or decannulation in children. 7,8,1419 …”
mentioning
confidence: 99%
“…Compared to our study, other investigators have demonstrated the utility of PSG in predicting decannulation success in pediatric patients with tracheostomy . These studies were not performed in rehabilitation patients and they tended to include younger patients with tracheostomy due to underlying airway abnormalities and pulmonary disorders with only a small proportion having neuromuscular related pathology.…”
Section: Discussionmentioning
confidence: 56%